2011
DOI: 10.1097/opx.0b013e3182206df2
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Hyperopia in Infants Using the PowerRefractor

Abstract: Accessory +4.50 diopter sphere spectacles appeared to successfully extend the operating range of the PR with cycloplegia, allowing for detection of high levels of hyperopia that occurred in a large proportion of 2-month old infants with adequate sensitivity and specificity compared with cycloplegic retinoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…High hyperopia was a common finding in the infants screened in this pediatric medical practice. The mean spherical equivalent refractive error, based on cycloplegic retinoscopy, in this sample of 473 infants was +2.54 ± 1.54 D. This is similar to samples of infants from previous studies, which find the mean refractive error in infants of similar age to range from +1.51 to +3.29 D, with SDs on the order of 0.94 to 1.60 D 10,11,26–29 . The prevalence of moderate hyperopia in this study, based on spherical equivalent classification, was 32.8%, and the prevalence of high hyperopia was 5.9%.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…High hyperopia was a common finding in the infants screened in this pediatric medical practice. The mean spherical equivalent refractive error, based on cycloplegic retinoscopy, in this sample of 473 infants was +2.54 ± 1.54 D. This is similar to samples of infants from previous studies, which find the mean refractive error in infants of similar age to range from +1.51 to +3.29 D, with SDs on the order of 0.94 to 1.60 D 10,11,26–29 . The prevalence of moderate hyperopia in this study, based on spherical equivalent classification, was 32.8%, and the prevalence of high hyperopia was 5.9%.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of moderate and high hyperopia was slightly lower compared with a screening similar in design to this current study and also conducted in Columbus, Ohio, in 2010. Satiani and Mutti 29 found that 61% of 2-month-olds had moderate hyperopia (≥+3.0 D), and 7.5% had high hyperopia (≥+5.0 D). In older infants, Ingram et al 30 found that 9.2% of 6-month-old infants had +5.25 D or more in at least one meridian, and the Multi-Ethnic Pediatric Eye Disease Study Group 31 found that 1.1% of African American 6-month-olds and 2.7% of Hispanic 6-month-olds had +5.00 D or more in the more hyperopic eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Satiani and Mutti applied accessory +4.50 D spectacles to extend the operating range of the PowerRefractor to detect highly hyperopic refractive errors and Nathan and Donohue modified Plusoptix referral criteria to enhance specificity of the device, whereas the original claim of the manufacturers about efficacy of photorefractors to determine the refractive errors in a defined range is still controversial. For instance, Matta and colleagues suggested that the Plusoptix S04 photoscreener is a very useful tool and vision screening programs likely will find this a useful option when examining children, while Ayse, Onder and Suheyla reported that Plusoptix S04 is not an accurate tool to estimate refraction in children.…”
mentioning
confidence: 99%
“…13 mm vertex distance) and the pupil plane could cause up to a 10% difference in the estimate. Some studies have used spectacle lenses when testing patients with large amounts of ametropia . These spectacles can bring the retinal defocus back into the linear operating range of the eccentric photorefractor, but they will also introduce magnification or minification of the pupil image depending on the lens power and vertex distance ( Figure ).…”
Section: Discussionmentioning
confidence: 99%